Exploration of learning styles by applying data mining technologies - Kaklauskienė, Danutė; Turskienė, Sigita (Lietuvos matematikos rinkinys, 2014)
The article deals with the possibilities to estimate students’ learning styles by applying data mining technologies and the methods suggested by the VARK learning styles model. Using the method of communication, the VARK learning style model in a chosen respondents’ set was estimated. This enables to formulate recommendations for an author of a distance learning course concerning possibilities of personalisation of a particular distance learning course. The concept-baseddata model was chosen to model the research data. The data of the designed e-test data base was processed by applying five stages of data mining.
Keywords: learning style; VARK learning styles model; data mining technologies